Tinjauan Maqashid Syariah terhadap Penyelesaian Klaim Produk Asuransi Jiwa Brilliance Hasanah Sejahtera di PT. Sun Life Financial Indonesia Cabang Medan - Indriani, Rizki; Sudiarti, Sri; Syahriza, Rahmi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
This study aims to determine the process of resolving claims for the Brilliance Hasanah Sejahtera product and to review it from the Maqashid Syariah aspect. The type of research used is descriptive research with a qualitative approach, namely research that provides an overview of the situation being studied in the form of a narrative description. The conclusion of this study is that the settlement of Brilliance Hasanah Sejahtera life insurance claims is in accordance with the specified conception which consists of notification of claims, submission of claim files, investigation of claim files, and payment of claims. Then in the process of settlement of Brilliance Hasanah Sejahtera life insurance claims in terms of maqashid sharia aspects, PT Sun Life Financial Indonesia Medan branch has realized maqashid sharia in the aspects of hifzh ad-din (property protection) and social benefit. The forms of hifzh ad-din (property protection) in the settlement process for Brilliance Hasanah Sejahtera life insurance claims at PT Sun Life Financial Indonesia Medan branch are: the false. Second, the management of claim funds in the form of tabarru funds is issued with sharia values ​​and does not contain elements of usury. Third, the administration of fund claims can be quickly provided to customers because the investigation of claims submission is carried out in a fast, responsive and strict procedure so that handling feels safe for customers and the company. And fourth, claims for payment of funds are made by transferring to each customer's account, so there is no need to worry about fraud or elements of gharar. However, the hifzh ad-din (property protection) aspect in the claim settlement process cannot be separated from other aspects of maqashid sharia which include hifzh ad-din (religious protection), hifzh an-nafs (life protection), hifzh al-aql (protection of reason) and hifzh an-nasl (protection of offspring) because all aspects of maqashid sharia influence one another. In the realization of the benefit of the existing maqasyid sharia values, the level lies at the first level, namely dharuriyat. Keywords : maqashid syariah, claims, life insurance, brilliance hasanah sejahtera.